ANALISIS BUTIR SOAL UJIAN SEMESTER GANJIL PELAJARAN KIMIA KELAS XI IPA SMA NEGERI 10 PEKANBARU TAHUN PELAJARAN 2013/2014 - Hasanah, Iswatul Hasanah Iswatul; Copriady, Jimmi Copriady Jimmi; Thaib, Armiyus Thaib Armiyus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study aimed to determine the quality of odd semester exam chemistry lesson for class XI IPA SMAN 10 Pekanbaru in academic year 2013/2014 viewed from relevance of indicator item and distribution of the cognitive taxonomy Bloom, level of difficulty, discrimination index, distracter effectiveness, test item validity, reliability. This research is descriptive ex post facto. Population includes all students in grade XI IPA SMAN 10 as 177 students. Sample consisted 96 students from 27% upper group and 27% lower group. The result from relevance item of indicator showed that from 40 test items there were 97,5% relevance to the test indicator and 2,5% were not relevance to the test indicator. The result from distribution of the cognitive taxonomy Bloom there was comparison C1:C2:C3:C4:C5:C6 is 15%:45%:40%:0%:0%:0% respectively. The result of analysis from level of difficulty there was 12,5% easy test item, 82,5% was medium and 5% was difficult. Furthermore the discrimination index there was 2,5% so bad test item discrimination, 15% bad discrimination, 32,5% medium discrimination, and 50% good discrimination. Viewed from the distracter effectiveness 42,5% had good function and 57,5% could not do their function well. Analysis of test item validity there were 85% valid and 15% were not valid. Reliability of the test was r11 = 0,86. Based on the result of this test can be said to have a low quality with classification readmission items obtained 27,5% items received, 70% repaired, and 2,5% rejected. Key Words: Analysis of test item, Test Â item validity, Reliability, Semester exams test